1997
DOI: 10.1002/hep.510260603
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, histological, and virological features of hepatitis C virus carriers with persistently normal or abnormal alanine transaminase levels

Abstract: This study was aimed to evaluate demographic, clinical, histological, and virological characteristics of 46 hepatitis C virus (HCV) carriers with persistently normal alanine transaminase (ALT) levels and to compare the results with those obtained in a group of 52 HCV-RNA-positive patients with elevated ALT levels. Subjects with normal ALT were more often females (P < .001), were more likely to be asymptomatic (P < .001), and have a lower incidence of risk factors for HCV transmission (P < .01). All patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
71
7
5

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(101 citation statements)
references
References 8 publications
18
71
7
5
Order By: Relevance
“…Contrary to previous reports, 16,27 our study shows no sex difference between the persistently normal and abnormal ALT groups, which might be a limitation of our study. However, based on multivariate analysis, sex was not found to be a confounding variable for fibrosis progression.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to previous reports, 16,27 our study shows no sex difference between the persistently normal and abnormal ALT groups, which might be a limitation of our study. However, based on multivariate analysis, sex was not found to be a confounding variable for fibrosis progression.…”
Section: Discussioncontrasting
confidence: 99%
“…Using the revised scoring system we have shown significantly less severe portal inflammation, piecemeal necrosis, and lobular inflammation as well as degree of fibrosis, and incidence of cirrhosis in patients with persistently normal ALT compared with patients with abnormal ALT. Similar results were reported by other investigators, 14,15 which are in contrast to the findings of at least 1 study 16 showing moderate to severe disease in persistently normal ALT patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation could be of clinical relevance, because presently the questions of (1) whether or not patients with persistently normal aminotransferases should undergo liver biopsy and (2) the therapeutic management of these patients are hotly debated. 47,48 Most of the patients with normal aminotransferase levels have mild degrees of inflammation with mild or no fibrosis. However, recent large-scale case studies have shown that a considerable percentage of patients with normal ALT levels have stage 3 or 4 liver fibrosis (reviewed by Bacon 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…The extent of liver cell necrosis and degree of elevated ALT level do not always correlate, and ALT measurements may fail to identify patients with necro-inflammatory activity or fibrosis, as seen in hepatitis C [12,13]. In addition, the ALT activity may vary with body mass index, sex, abnormal lipid and carbohydrate metabolism as well as the time of the day [14,15].…”
Section: Fallacies Of Alt Levels For Prediction Of Liver Injury and Tmentioning
confidence: 99%